A new mechanism shapes the naïve CD8+ T cell repertoire: the selection for full diversity. (May 2017) - Gonçalves, Pedro; Ferrarini, Marco; Molina-Paris, Carmen; Lythe, Grant; Vasseur, Florence; Lim, Annik; Rocha, Benedita; Azogui, Orly
Highlights: The diversity of the mouse naïve CD8 + TCR repertoire. We directly sequenced Tcrb chain from naïve CD8 + single cells. We show that the average clone size in the periphery is 1.1 cell. The number of diverse TCRs approaches the total number of naïve CD8 + T cells. The peripheral repertoires are shaped by a strong selection for TCR diversity. Abstract: During thymic T cell differentiation, TCR repertoires are shaped by negative, positive and agonist selection. In the thymus and in the periphery, repertoires are also shaped by strong inter-clonal and intra-clonal competition to survive death by neglect. Understanding the impact of these events on the T cell repertoire requires direct evaluation of TCR expression in peripheral naïve T cells. Several studies have evaluated TCR diversity, with contradictory results. Some of these studies had intrinsic technical limitations since they used material obtained from T cell pools, preventing the direct evaluation of clonal sizes. Indeed with these approaches, identical TCRs may correspond to different cells expressing the same receptor, or to several amplicons from the same T cell. We here overcame this limitation by evaluating TCRB expression in individual naïve CD8 + T cells. Of the 2269 Tcrb sequences we obtained from 13 mice, 99% were unique. Mathematical analysis of the data showed that the average number of naïve peripheral CD8 + T cells expressing the same TCRB is 1.1 cell. Since TCRA co-expression studies could only increase repertoire diversity, these results reveal that the number of naïve T cells with unique TCRs approaches the number of naïve cells. Since thymocytes undergo multiple rounds of divisions after TCRB rearrangement and 3–5% of thymocytes survive thymic selection events the number of cells expressing the same TCRB was expected to be much higher. Thus, these results suggest a new repertoire selection mechanism, which strongly selects for full TCRB diversity.